The Difference of Despression Level Before and After Keroncong Music Therapy in the Elderly - Raufuddin, Raufuddin (Universitas Airlangga, 2021)
Introduction: coming to an old age a person will experience physical, psychological, and biological setbacks. Psychological deterioration which is often found in the elderly is depression (Purbowinoto, 2010). One of the non-pharmacological therapies that can be applied to reduce depression levels in the elderly is to use keroncong music therapy. The purpose of this study was to determine the differences in depression levels in the elderly before and after being given keroncong music therapy at UPTD Griya Werdha Jambangan Surabaya.Method: the method used was analytical pre-experimental research with pre testpost test design. The independent variable in this study was depression in the elderly, while the independent variable was keroncong music therapy. The population is 40 elderly with 36 samples in the UPTD Griya Werdha Jambangan Surabaya taken using purposive sampling techniques. The data was taken using a questionnaire. Data analysis used the Wilcoxon Rank Test statistical test.Results: from the results of the study, it was found that there was a difference in the levels of depressionin the elderly before and after being given keroncong music therapy at UPTD Griya Werdha Jambangan Surabaya with a significant value of = 0.0001 lower than p= 0.05 (p <α). Before the therapy or treatment, most of the elderly experienced depression levels with as many as 11 respondents (30.6%) and after the treatment most of them experienced depression level with as many as 16 respondents (44.4%).Conclusion: it could be concluded that there was a difference in levels of depression in the elderly before and after being given keroncong music therapy at UPTD Griya Werdha Jambangan Surabaya. For this reason, music therapy can be an option to decrease the depression level in the elderly at UPTD Griya Werdha Jambangan Surabaya.